مؤتمر الصومام من خلال كتابات علي كافي وبن يوسف بن خدة - متين عبد العزيز; د/ قفاف عبد الرحمان (My University, 2023)
الملخص: يعتبر مؤتمر الصومام بداية مرحلة حاسمة في تطور كفاح الشعب الجزائري من أجا تحقيق استقلاله وحريته وتظهر أهميته في أنه أول محاولة لإعطاء مفهوم متماسك للثورة وحدد الأهداف والوسائل النضالية في بيان سياسي مهم وهذا يذكرنا في تاريخ 20 اوت 1956 : فترات تاريخنا المجيد لكونه يرتبط بالجلسات التقييمية الأولى التي عقدتها جبهة التحرير الوطني بعد عامين من الكفاح المسلح والحديث عن مؤتمر الصومام فهي تبرز إحدى أعظم صفحات تاريخنا المجيد ونرد الجميل الى العضماء الذين فجروا ثروة الفاتح نوفمبر 1954 سواء الذين استشهدو في ساحات المعارك أو أولئك الذين واصلوا الجهاد بعد الاستقلال في إطار بناء الدولة الجزائرية الحديثة. Abstract The Soummam Conference is considered the beginning of a decisive stage in the development of the struggle of the Algerian people to achieve their independence and freedom, and its importance appears in that it is the first attempt to give a coherent concept to the revolution and define the goals and means of struggle in an important political statement, and this reminds us of the date of August 20, 1956. The periods of our glorious history because it is linked to the first evaluation sessions held by the National Liberation Front after two years of armed struggle Talking about the Soummam Conference, it highlights one of the greatest pages of our glorious history and we return the favor to the members who blew up the wealth of the conqueror in November 1954, whether those who were martyred on the battlefields or those who continued jihad after independence within the framework of building the modern Algerian state